Building lower secondary school students’ interest and motivation towards science: The role of students’ worksheet in particles of substance and living organism - Kinanthi, Bilqis Rahma; Habiddin, Habiddin; Sumari, Sumari; Suwasono, Purbo; Santosa, Santosa (Universitas Negeri Malang, 2023)
Science learning that only focuses on the assignment and exposure to material can cause students to be less interested and less motivated to learn science. One example of a student's worksheet (Lembar Kerja Peserta Didik in Indonesian, LKPD) that effectively attracts students' learning interest is using the LKPD format in comics because it combines visual elements with words. The content of comics can be arranged based on scientific events and dialogues from everyday life, helping students understand the relationship between science and the context of everyday life. This study aims to determine the role of comic-based LKPD in attracting interest and motivation to learn science for grade 9B students of SMPN 11 Malang. This research is included in quantitative descriptive research using survey methods. The data collection for this study was done through a questionnaire distributed through Google Forms with a Likert interval scale. The results of the questionnaire data analysis show that 81.83% of students strongly agree that comic-based LKPD attracts their interest and motivation to learn.